Promotion System Design Whit e-CRM at Univeristas Harapan Medan - Syahputra, Edy Rahman; Sembiring, Boni Oktaviana (Al'adzkiya International of Computer Science and Information Technology (AIoCSIT) Journal, 2023)
The number of new students is very important in the continuity of the running of the organization, because after all a private higher education institution still relies on its income from student tuition fees. To be able to attract new student candidates, UnHar Medan has taken steps to anticipate higher education competition. In order to create, improve and maintain its competitiveness, UnHar Medan must carry out the right promotion. Promotional activities carried out by distributing brochures and visiting schools for direct promotions. This is certainly less effective in the middle of the current pandemic. To help UnHar Medan in building a system-based promotion system, the researchers designed a promotion system. The method in designing the system uses e-CRM with the process of finding problems and solutions using the PIECES method. In designing a business process system using UML. The research result is a web-based promotion application system design. Keyword : Promotion, e-CRM, PIECES, UML